Determination of the Harvesting factors of Independent Smallholder Oil Palm Estate - Lovely, Afroza Khanam; Fatimah, Mahmud; M. H., Rohaya (Academic Research Online Publisher, 2015)
This study investigates the factors of oil palm fruit harvesting management. Focus was given to the Independent Smallholder Estate (ISE) and the data was collected through survey on the farmers, dealers and processing mill. It is found that the major factors that affect palm oil quality are harvesting method, harvesting intervals and transportation delay time. To analyse different factors the data was collected on fruit quality such as ripeness, fruit bruising during harvesting from different estates. It was found that over ripe fruit produces more bruising and loose fruit which results higher free fatty acid content in the oil which is the major factor for oil quality. On the other hand under ripe fruit produces low yield of oil. Harvesting method such as manual or using mechanical tools makes a difference on fruit bruising and also on the harvesting cost.